1988
DOI: 10.1128/mcb.8.11.4821
|View full text |Cite
|
Sign up to set email alerts
|

A Mup promoter-thymidine kinase reporter gene shows relaxed tissue-specific expression and confers male sterility upon transgenic mice.

Abstract: A hybrid gene was made by fusing the 2.2-kilobase 5' promoter region of a mouse group 1 major urinary protein (Mup) gene to the coding region of the herpes simplex virus type 1 thymidine kinase gene (HSV tk) and introduced into the genomes of mice by microinjection. Transgenic Go males were sterile, or when fertile did not transmit the foreign gene, and the transgenic male descendants of Go females were also sterile. Seven "lines" were established by breeding from Go females and their transgenic female desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
50
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 51 publications
3
50
2
Order By: Relevance
“…16 Southern blotting revealed transmission of the THP-HSV1-tk transgene to subsequent generations with no apparent loss of copy number (data not shown). Transgenic positive mice had no obvious phenotypic abnormalities.…”
Section: Hsv1tk Is Expressed In the Tal Of Thp-hsv1tk Transgenic Micementioning
confidence: 99%
“…16 Southern blotting revealed transmission of the THP-HSV1-tk transgene to subsequent generations with no apparent loss of copy number (data not shown). Transgenic positive mice had no obvious phenotypic abnormalities.…”
Section: Hsv1tk Is Expressed In the Tal Of Thp-hsv1tk Transgenic Micementioning
confidence: 99%
“…For example, most transgenic male mice expressing the herpes simplex virus type 1 thymidine kinase reporter gene in their testes were infertile [7]. Male infertility of transgenic mice carrying the mouse interferon-β gene [8] and of transgenic rats carrying the rat c-myc gene [9] under the control of the metallothionein enhancer-promoter has also been reported.…”
mentioning
confidence: 99%
“…58: [544][545][546][547][548][549][550][551] 2012) A suicide gene system, herpes simplex virus type 1 thymidine kinase (HSV1-TK) and its specific substrate, ganciclovir, is widely used for cancer therapy [1,2]. However, previous investigators also reported that HSV1-TK proteins are likely to play a toxic role in the developing mouse male germ cells in the absence of the nucleoside analog, ganciclovir, to induce defects in cell proliferation [3][4][5][6]. The major histological defects of HSV1-TK transgenic mice appeared to be an abnormal nuclear morphology of elongating spermatids and electron microscopy observation disclosed insufficient chromatin condensation and abnormal acrosome structures [4].…”
mentioning
confidence: 99%